2011
DOI: 10.1016/j.ijpsycho.2011.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Emotional scenes and facial expressions elicit different psychophysiological responses

Abstract: We examined if emotional faces elicit physiological responses similar to pictures of emotional scenes. Forty one students viewed emotional scenes (negative, neutral, and positive) and emotional faces (angry, neutral, and happy). Heart rate, orbicularis oculi and electrodermal activity were measured continuously, and the startle reflex was elicited. Although the patterns of valence and arousal ratings were comparable, physiological response patterns differed. For scenes we replicated the valence-specific modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
92
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 68 publications
15
92
0
2
Order By: Relevance
“…This interpretation is supported by work in the healthy brain 10, 11. The subjective experience of emotion is likely to be integral to the internalization of observed emotional states in others during emotional contagion.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This interpretation is supported by work in the healthy brain 10, 11. The subjective experience of emotion is likely to be integral to the internalization of observed emotional states in others during emotional contagion.…”
Section: Discussionmentioning
confidence: 83%
“…Central to understanding affective empathy is the concept of interoceptive inference, which proposes that emotional awareness entails reciprocal feedback between somatic physiology and the cognitive interpretation of those signals 8, 9. Emotional stimuli produce autonomic effects including modulation of heart rate, but different emotions do not reliably produce specific individual patterns of autonomic responses, and they are therefore hypothesized to relate to arousal and intensity rather than emotion category 10, 11. Stimulus onset induces a cardiac orienting deceleration, which is modulated by affective content, with greater cardiac deceleration accompanying higher emotional valence 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with autism spectrum disorders (ASDs; including autism and Asperger's Syndrome) 1 display marked impairments in social interaction (poor social-emotional reciprocity, deficits in the use of non-verbal communication such as eye-gaze and facial expression) and the presence of repetitive and stereotyped behaviours (APA, 2000(APA, , 2013. Consistent with diagnostic criteria of marked deficits in reciprocal social interaction, individuals with ASDs generally have impaired emotion processing and recognition.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the expected modulation of the startle reflex by emotional facial expressions only for subgroups of participants (i.e., women; Anokhin & Golosheykin, 2010), while others have failed to demonstrate the expected effect altogether (Alpers, Adolph, & Pauli, 2011). It has been argued that these inconsistent findings might relate to the nature of emotional expressions (Hess, Sabourin, & Kleck, 2007;Springer, Rosas, McGetrick, & Bowers, 2007): facial expressions of emotions do not only carry affective information but also a social message (see also Keltner & Haidt, 1999;Paulus & Wentura, 2013).…”
mentioning
confidence: 99%